Radiation doses with various body weights of phantoms in brain 128-slice MDCT examination. (14th June 2019) - Lin, Hung-Chih; Lai, Te-Jen; Tseng, Hsien-Chun; Wang, Ching-Hsiang; Tseng, Yen-Ling; Chen, Chien-Yi
Abstract: The effective dose (HE ) and organ or tissue equivalent dose (HT ) for use in brain computed tomography (CT) examinations with various body weights were evaluated. Thermoluminescent dosimeters (TLD-100H) were inserted into Rando and five anthropomorphic phantoms. These phantoms were made of polymethylmethacrylate (PMMA), according to the specifications of ICRU 48, with masses from 10 to 90 kg. Brain CT examinations were conducted, scanning the maxillae from the external auditory meatus to the parietal bone using a 128-slice multi-detector CT (MDCT) scanner. To reduce errors, three independent trials were conducted. Calculated HE, TLD, based on the weighting factor recommended by ICRP 103, was 1.72 ± 0.28 mSv, which slightly exceeds the HE, DLP of 1.70 mSv, that was calculated from the dose–length product (DLP) of the Rando phantom. This experiment yielded HE, TLD values of ICRP 103 from the highest 1.85 ± 0.28 (90 kg) to the lowest 1.47 ± 0.22 (10 kg) mSv. HE, TLD (mSv) = 5.45×10 −3 W(kg) + 1.361, with an R 2 of 0.87667. Using the DLP protocol, HE, DLP was estimated from CTDIvol that was recorded directly from the console display of the CT unit and multiplied by the conversion coefficient ( k ) recommended by the ICRP 103. Finally, the experimental results obtained herein are compared with those in the literature. Physicians should choose and adjust protocols to prevent the exposure of patients to unnecessary radiation, satisfying the as low as reasonably achievable (ALARA) principle. These findings will be valuable to patients, physicians, radiologists and the public.